2006
DOI: 10.1021/jm058288w
|View full text |Cite
|
Sign up to set email alerts
|

Second Generation, Orally Active, Antimalarial, Artemisinin-Derived Trioxane Dimers with High Stability, Efficacy, and Anticancer Activity

Abstract: In only two steps and in 63% overall yield, naturally occurring 1,2,4-trioxane artemisinin (1) was converted into C-10-carba trioxane conjugated diene dimer 4. This new dimer was then transformed easily in one additional 4 + 2-cycloaddition step into phthalate dimer 5, and further modification led to bis-benzyl alcohol dimer 7 and its phosphorylated analogues 8 and 9. Bis-benzyl alcohol dimer 7 is the most antimalarially active in vitro, 10 times more potent than artemisinin (1). Bis-benzyl alcohol dimer 7 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 31 publications
2
72
1
3
Order By: Relevance
“…The increase in potency varies from 10-to 200-fold [106,127,128,[130][131][132]. Artemisinin dimers have also been shown to be as or even more potent than some chemotherapeutic agents, such as doxorubicin [133], and much less toxic to normal cells than cancer cells [130,134]. Posner et al [135] reported a high therapeutic index (>150) for some of the dimers they synthesized.…”
Section: Artemisinin Dimers and Trimersmentioning
confidence: 99%
“…The increase in potency varies from 10-to 200-fold [106,127,128,[130][131][132]. Artemisinin dimers have also been shown to be as or even more potent than some chemotherapeutic agents, such as doxorubicin [133], and much less toxic to normal cells than cancer cells [130,134]. Posner et al [135] reported a high therapeutic index (>150) for some of the dimers they synthesized.…”
Section: Artemisinin Dimers and Trimersmentioning
confidence: 99%
“…One study that analyzed 55 cell lines of the Developmental Therapeutics Program of NCI, National Institutes of Health, showed that artesunate, the semisynthetic derivative of artemisinin, has anti-cancer activities against leukemic, colon, melanoma, breast, ovarian, prostate, central nervous system, and renal cancer cell lines (12). More-over, the highly stable artemisinin-derived trioxane dimmers was shown to inhibit the growth of and selectively kill several human cancer cell lines without inducing cytotoxic effects on normal neighboring cells (13). The molecular mechanism and gene expression changes that mediate the anti-proliferative activity of artemisinin are not well characterized.…”
mentioning
confidence: 99%
“…Later, two unsymmetric dimers were prepared and found to be comparable to arteether when tested in K-173-infected mice [264] (Figure 32). Since the end of the 20th century, a number of new types of deoxoartemisinin dimers ( Figure 33) have been developed [265][266][267][268][269][270][271][272]. Most compounds had both antimalarial and antitumor activities.…”
Section: Dimers and Trimersmentioning
confidence: 99%